3-D Numerical Study of Cavitation Evolution Through A Butterfly Valve Model at Different Regulating Conditions - G. Zhang; X. Wu; Z. Y. Wu; H. T. Zhang; H. D. Kim; Z. Lin (Journal of Applied Fluid Mechanics)
Butterfly valves are critical control equipment widely used in transmission systems across various fields, including energy, water conservancy, materials and chemical industries, metallurgy, and aerospace engineering. Cavitation, induced when the local pressure is decreased to saturated vaporization pressure, is a common phenomenon in butterfly valves and causes severe damage to valve components. Numerical studies were conducted to explore the progression of dynamic cavitation in a butterfly valve under different actual conditions by using Large Eddy Simulation (LES) coupled with Schnerr-Sauer cavitation model.  The detailed evolution process of generation, development, and collapse was discussed by analyzing the corresponding vapor volume fraction. With the increase of valve opening, there is a corresponding increase in cavitation volume, leading to the rise of disturbance coefficient in full flow field as well as the decrease of shedding frequency of cavitation. The decline of shedding frequency of cavitation exhibits a sudden and pronounced drop at valve opening degree of 60%, which can be attributed to a shift in cavitation shedding behavior from unilateral to bilateral shedding. Periodic changes in cavitation evolution and the presence of attached cavitation on the upper surface of valve plate are obtained and discussed in detail. A comparative analysis of vortex distribution and structure within the flow field reveals insights into the spatial and temporal correlation between cavitation and vortices. The present study of the cavitation mechanism and the in-depth exploration of the evolution law of cavitation provide a clearer understanding of cavitation phenomenon, offering a reference for the structural optimization of butterfly valve in cavitation inhibition.